2012
DOI: 10.7150/ijms.4382
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Oral Anaerobic Bacteria and Otitis Media with Effusion

Abstract: Objective: In this study hypothesing the translocation of oral bacteria from oropharynx into the middle ear cavity may be involved in the pathogenesis of otitis media with effusion (OME), we aimed to investigate the presence and similarity of Fusobacterium nucleatum and Treponema denticola in saliva, nasopharyngeal secretion and the middle ear effusion samples from the children with OME.Methods: Totally 20 children with OME undergoing myringotomy and ventilation tube placement were attended. Stimulated saliva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
0
11
0
1
Order By: Relevance
“…We concluded that MFGM supplementation provided a protective effect against infections, especially AOM. Bacterial colonization of the upper airways has been suggested to be important for the pathogenesis in AOM [18], and not only nasopharynx cultures [19–21] but also cultures from saliva [22, 23] at onset of AOM correlate to otopathogens…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that MFGM supplementation provided a protective effect against infections, especially AOM. Bacterial colonization of the upper airways has been suggested to be important for the pathogenesis in AOM [18], and not only nasopharynx cultures [19–21] but also cultures from saliva [22, 23] at onset of AOM correlate to otopathogens…”
Section: Introductionmentioning
confidence: 99%
“…thereby, it is well acknowledged that microorganisms from the nasopharynx can reach the middle ear cavity via the eustachian tube and cause middle ear infection. in a previous study, using 16Sr RnA-based conventional PcR, F. nucleatum was detected in 11 (55 %) saliva, eight (40 %) nasopharyngeal and six (30 %) middle ear effusion samples (19). We hypothesize that the rate could be higher if more sensitive methods are used, such as the real-time PcR assay.…”
Section: Introductionmentioning
confidence: 77%
“…they belonged to a population of a previous study on the relationship between oral anaerobic bacteria and otitis media with effusion (19). Paraffin-stimulated saliva samples were collected immediately after clinical examination.…”
Section: Methodsmentioning
confidence: 99%
“…Su capacidad de degradar proteínas y modular la respuesta del huésped la hacen una bacteria evolucionada. Autores como Cortelli 24 han podido determinar que esta bacteria no necesita del diente para su presencia, pudiendo identificarla en recién nacidos y niños con dentición mixta, a nivel de lengua, mejilla y surco gingival; así también Topcuoglu 25 , determina que su translocación de zonas de la orofaringe, al oído podrían originar cuadros de infecciosos como otitis media con "derrame". Así también su presencia se intensificaría en pacientes con ciertos cuadros sistémicos, como la Diabetes tipo II, comprobado por Quinteros, 26 el cual determino que diabéticos tipo II con mal control glicémico, presentaban mayor presencia de periodontopatógenos como el.…”
Section: Discussionunclassified